The methodological principles of «Facility Management» - Vitrenko, L. (Ways to Improve Construction Efficiency, 2015)
The article investigates the issues of property management; highlights the main ways of implementation of foreign experience in the domestic practice; the use of technique «facility management» as a basic tool, which is essential to the fulfillment of all tasks of property management.